Seduced by a Steele - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Forged of Steele., 2020)
A notorious heartbreaker is about to meet his match...When the 'thief' caught driving his stolen vintage car turns out to be a stunning runaway heiress, Mercury Steele is conflicted. On the one hand, Sloan Donahue, broke and on the run from her tyrannical family, triggers the billionaire playboy's protective instincts. But she also triggers red-hot desire. Mercury refuses to think his simple seduction is becoming something deeper, especially when Sloan is keeping secrets...